2017
DOI: 10.1097/igc.0000000000001060
|View full text |Cite
|
Sign up to set email alerts
|

Preoperatively Assessable Clinical and Pathological Risk Factors for Parametrial Involvement in Surgically Treated FIGO Stage IB–IIA Cervical Cancer

Abstract: Endophytic clinical presentation and larger clinical tumor size (>3 cm) are independent risk factors for PMI in stage IB-IIA cervical cancer. Approximately 78% of the patients with a tumor size of more than 3 cm and endophytic presentation will require adjuvant chemoradiation for PMI following radical surgery. Considering clinical tumor presentation along with tumor size can enhance the physician's prediction of PMI in early-stage cervical cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 42 publications
4
26
2
Order By: Relevance
“…Although parametrial invasion [10] and positive vaginal margin involvement [5,8,10] were more frequently associated with tumors ≥ 2 cm in diameter, some studies indicated no significant differences according to tumor size. Studies evaluating microinvasion observed during radical resection of the parametrium, which is the primary aim of radical surgery, showed that tumor size was an independent predictor of parametrial spread according to regression analyses [1,3,14]. In our study, parametrial invasion was only detected in eight patients.…”
Section: Discussionsupporting
confidence: 39%
“…Although parametrial invasion [10] and positive vaginal margin involvement [5,8,10] were more frequently associated with tumors ≥ 2 cm in diameter, some studies indicated no significant differences according to tumor size. Studies evaluating microinvasion observed during radical resection of the parametrium, which is the primary aim of radical surgery, showed that tumor size was an independent predictor of parametrial spread according to regression analyses [1,3,14]. In our study, parametrial invasion was only detected in eight patients.…”
Section: Discussionsupporting
confidence: 39%
“…We applied these extracted factors only to stage IB1, IB2, IIA1 and IIA2 cases and excluded IIB, as clinical T2b cervical cancer requires an adaptation of complete Type III RH or CCRT. When all three factors exceeded the identified thresholds (age > 50 years and tumor size >40 mm) or were positive (common lymph node In a previous report, Canaz et al 7 identified two predictive factors for PMI: endophytic presentation and a tumor size larger than 3 cm. However, in that study, PMI occurred in 29.1% of subjects with stage IB-IIA disease, a higher rate than that in our study or other reports.…”
Section: Discussionmentioning
confidence: 98%
“…In a previous report, Canaz et al identified two predictive factors for PMI: endophytic presentation and a tumor size larger than 3 cm. However, in that study, PMI occurred in 29.1% of subjects with stage IB–IIA disease, a higher rate than that in our study or other reports.…”
Section: Discussionmentioning
confidence: 99%
“…Complex clinical scenarios such as the shallowness or disappearance of the vaginal fornix in post-menopausal women, the bulky tumor extending to the vaginal wall, or the inflammation surrounding the tumor make it difficult to determine the degree of vaginal invasion. Canaz et al stated that vaginal invasion can be overestimated by clinical staging in comparison with the pathologic examination 23. Qin et al reported the accuracy of stage IIA as only 35.3% and that more than 50% of the patients with stage IIA were clinically overstaged 21.…”
Section: Discussionmentioning
confidence: 99%